Malaises organisationnels : place, plainte et pente dangereuse - Gilbert de Terssac (La Nouvelle Revue du Travail)
When organisational choices or decisions are imposed without dialogue, when debate about service orientations is stifled, when senior management advocates certain values that it does not respect itself, when rules are constantly broken because they are applied wrongly, the entity in question can be called a “wounded organisation”. When individuals no longer do their work correctly or provide the service that the public expects, when their roles come under fire due to reorganisations for which they were unable to prepare themselves, when they can no longer communicate with managers to get them to recognise the value of the work being done, when long-standing benchmarks disappear because the group’s action is being questioned – these are all examples of “organisational wounds”. Organisational malaise is the product of the encounter between a wounded organisation circumscribing organisational activities and the wounds featured in the present study, which comes from two years of research in a local authority.